Laser cutting and welding technologies advance.
New techniques in laser cutting and welding are opening doors in automotive and medical manufacturing applications. More powerful, flexible systems for robotic laser processing and five axis laser cutting are being used to cut the newer high strength steels in today's automobiles and for laser cutting and welding processes in medical device manufacturing.